Current Clinical Treatments and Challenges for Cardiovascular Diseases: From Therapeutic Expansion to Individualized Care - Christos Kourek; Georgios Bouras (Journal of Clinical Medicine, 2026)
This Editorial closes the Special Issue “Current Clinical Treatments and Challenges for Cardiovascular Diseases”, which was conceived to examine contemporary cardiovascular care at the point where therapeutic progress meets persistent clinical uncertainty [...]